The Aesthetics of Poetic Function in Al-Gharaniq Al-‘Ulaa: A Structural Analysis Based on Jakobson’s Theory - Asep Adli Azhari Nursyahbani; Akhmad Kholil (Raja Zulkarnain Education Foundation, 2025)
This study aims to examine the poetic function in Khazal Al-Majidi's poem Al-Gharaniq Al-'Ulaa using a structural approach based on Roman Jakobson's theory of language function. The analysis focuses on three primary linguistic levels: phonology, syntax, and semantics. Through this approach, the study explores sound elements such as assonance and alliteration, sentence structure, and symbolic meaning in the poem, contributing to the formation of aesthetic effects and complex poetic messages. The data collection procedures in this study involved several stages: (1) reading the entire poem Al-Gharaniq Al-’Ulaa; (2) identifying lines related to phonological features; (3) identifying lines related to syntactic structures; (4) identifying lines that reflect semantic structures; (5) selecting and reducing data to ensure relevance and focus; (6) interpreting the selected data descriptively; and (7) presenting the findings in the form of research results, followed by drawing conclusions. The data were analyzed using a structural approach based on Roman Jakobson's language function theory. The results show that the poem utilizes intensive repetition of vowel and consonant sounds to create certain rhythms and emotional nuances. At the syntactic level, a flexible and stylish grammatical structure is found, supporting the delivery of meaning both implicitly and explicitly. Meanwhile, from a semantic perspective, the poem contains strong metaphors and symbolism, especially in the representation of